2017
DOI: 10.3390/en10122122
|View full text |Cite
|
Sign up to set email alerts
|

An Improved Lubrication Model between Piston Rings and Cylinder Liners with Consideration of Liner Dynamic Deformations

Abstract: Abstract:The friction pair of piston rings and cylinder liner is one of the most important friction couplings in an internal combustion engine. It influences engine efficiency and service life. Under the excitation of piston slaps, the dynamic deformation of cylinder liner is close to the surface roughness magnitudes, which can affect the friction and lubrication performance between the piston rings and cylinder assemblies. To investigate the potential influences of structural deformations to tribological beha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 22 publications
(52 reference statements)
0
6
0
Order By: Relevance
“…The lubrication system is a crucial system to guarantee the safe and reliable operation of a diesel engine. The poor working conditions of a lubrication system can lead to abnormal wear or even some major safety accidents [23,24], e.g., cylinder score and the journal sticking of a diesel engine. Accordingly, the lubrication system was taken as the research object in our study to simulate the faults and illustrate the proposed engine fault detection approach.…”
Section: Description Of the Engine Test Cellmentioning
confidence: 99%
“…The lubrication system is a crucial system to guarantee the safe and reliable operation of a diesel engine. The poor working conditions of a lubrication system can lead to abnormal wear or even some major safety accidents [23,24], e.g., cylinder score and the journal sticking of a diesel engine. Accordingly, the lubrication system was taken as the research object in our study to simulate the faults and illustrate the proposed engine fault detection approach.…”
Section: Description Of the Engine Test Cellmentioning
confidence: 99%
“…It is clear that a liner is not ideally circular, and two different conditions of lubrication (i.e., fully flooded and starved) usually coexist in an RLC engine cycle [21][22][23]. This is because liner deformation at assembly and service stages is inevitable [24], and the lubricant supplied to the ring is time-varying and usually insufficient at some points of the engine cycle [25]. Therefore, this study provides a comprehensive mathematical model to analyze the frictional characteristics of a groove textured RLC by considering liner deformation and the coexistence of the two different lubrication conditions in an engine cycle.…”
Section: Of 21mentioning
confidence: 99%
“…According to the principle of flow conservation, a flow balance equation should be satisfied for the front control volume [37]. The flow balance equation is given as: q in_ave − q en_ave = q front_ave (24) By submitting Equations (20)~ (22) into Equation 24, the following expression can be obtained.…”
Section: Lubrication Conditionmentioning
confidence: 99%
“…Research has shown that for every 10% increase in engine friction loss, fuel consumption would increase by 3% to 5%, and the engine's effective output power would also decrease accordingly. The irregular deformation of the cylinder bore will lead to an increase in cylinder clearance, which will cause an increase in piston-knocking noise [8,9]. Therefore, rationalizing the design of the cylinder bore pattern, reducing the friction power and the peak knocking kinetic energy of the PRCB system, is of great significance to improving the economy and NVH performance of diesel engines.…”
Section: Introductionmentioning
confidence: 99%